Cranial nerve injuries in adult faciomaxillary trauma: prospective study in a tertiary referral centre - Murari, Gowrishankar; Duraipandi, Kannathal; Muthusamy, Sankara Subramanian (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Cranial nerve injury is often an overlooked aspect of faciomaxillary trauma. Most of these injuries do require active intervention in the acute stage. Cranial nerve injuries require long-term management, repeated surgical procedures or reconstructive measures. Methods: The study was conducted for one-year prospective study of clinical evaluation of 180 patients with faciomaxillary injuries from May 2017 to May 2018 at tertiary care hospital. There were 154 male patients (86.3%) and 26 (13.7%) female patients. The patients from the age of 18 onwards were included in the study group after obtaining consent. A number of parameters, including age, gender, injury of cranial nerve injuries, sensory and motor deficit in relation to soft tissue trauma and bone fracture were evaluated. The objective of the present study is to evaluate early management and document the frequency of cranial nerve injuries associated with maxillofacial trauma. Results: In 180 cases of faciomaxillary trauma, 60 patients presented with cranial nerve injuries including olfactory, optic, trigeminal, facial, vestibulocochlear, abducens nerve either as an isolated or combined cranial nerve injuries. Out of which most common nerve to get injured was trigeminal followed by facial nerve observed in our study. Conclusions: Cranial nerve injury in maxillofacial trauma is significant and it should be addressed at the time of treatment so that quality of life of patient is improved by getting back his sensory and motor functions of the injured nerves.